Relationship between smiling and laughter in humans (Homo sapiens): testing the power asymmetry hypothesis - Mehu, M; Dunbar, R (Karger, 2008)
The power asymmetry hypothesis claims that individuals should have distinct signals of appeasement/affiliation and play when status difference is high, whereas these signals should overlap in egalitarian interactions. Naturalistic observations were conducted on humans interacting in groups that differed in terms of age composition (and presumably social status). Three affiliative behaviours were recorded by focal sampling: spontaneous smiles, deliberate smiles and laughter. Interestingly, young men showed significantly higher proportions of deliberate smiles in comparison to laughter when interacting with people of a different age class than when interacting in same-age groups. The pattern of affiliative behaviours in women remained unaffected by the age composition of groups. This partly supports the power asymmetry hypothesis and suggests that in men, deliberate smiles could play a role in the regulation of hierarchical relationships.